2016
DOI: 10.1063/1.4940397
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Accurate higher-order van der Waals coefficients between molecules from a model dynamic multipole polarizability

Abstract: Due to the absence of the long-range van der Waals (vdW) interaction, conventional density functional theory (DFT) often fails in the description of molecular complexes and solids. In recent years, considerable progress has been made in the development of the vdW correction. However, the vdW correction based on the leading-order coefficient C6 alone can only achieve limited accuracy, while accurate modeling of higher-order coefficients remains a formidable task, due to the strong non-additivity effect. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 59 publications
(42 reference statements)
1
36
0
Order By: Relevance
“…Compared to the original SFA, the MSFA yields the dynamic dipole polarizability in better agreement with the TDHF values for fullerene C 60 , in particular in the important low-frequency region. This accuracy is consistent with a recent application to diatomics and small molecules 50 , where it was found that the MSFA yields accurate vdW coefficients, with a MARE of 6% for C 6 , 5% for C 8 , and 7% for C 10 . This small relative error difference is largely due to the fact that the electron density on the surface of fullerenes and in sodium clusters is not rapidly varying, but it is for small molecules, in particular diatomics.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Compared to the original SFA, the MSFA yields the dynamic dipole polarizability in better agreement with the TDHF values for fullerene C 60 , in particular in the important low-frequency region. This accuracy is consistent with a recent application to diatomics and small molecules 50 , where it was found that the MSFA yields accurate vdW coefficients, with a MARE of 6% for C 6 , 5% for C 8 , and 7% for C 10 . This small relative error difference is largely due to the fact that the electron density on the surface of fullerenes and in sodium clusters is not rapidly varying, but it is for small molecules, in particular diatomics.…”
Section: Discussionsupporting
confidence: 72%
“…As a result, the errors of the two models are nearly size-independent, as confirmed by vdW coefficients for nanoclusters 49,50,52 . More recently, one of the present authors (JT) 50 applied the solid-sphere model to calculate both the leading-order and higherorder vdW coefficients between small molecules, within the modified single-frequency approximation (see discussion below). The results are in very good agreement with expensive TDMP2 or TDHF calculations, with mean absolute relative errors of 6% for C 6 , 5% for C 8 , and 7% for C 10 .…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, semilocal DFT often fails to describe this process, because the long-range vdW interaction is missing in semilocal DFT. Many attempts 25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54] have been made to capture this long-range part, such as nonlocal vdW-DF functional 41 and density functional dispersion correction 55,56 . It has been shown that with a proper dispersion correction, the performance of ordinary DFT methods can be significantly improved 26 .…”
Section: Vdw Coefficientsmentioning
confidence: 99%
“…The first property is very important for surface energy calculations, while the second is helpful in capturing the van der Waals interactions, [72][73][74][75][76][77][78][79] as demonstrated by the excellent performance of the TM functional for lattice constants (Table II) and cohesive energies (Table V). Recently, we have also assessed 80 the TM functional on diverse molecular properties and found that it has a similarly good accuracy for atoms and molecules as for solids.…”
Section: Discussionmentioning
confidence: 99%